Efficacy of 5-aminolevulinic acid photodynamic therapy versus observation for cervical low-grade squamous intraepithelial lesion with type 3 transformation zone - Ruizhe Chen; Junfen Xu; Chun Ye; Lingjia Lu; Ying Li; Lingfang Wang; Xiaodong Cheng; Yunfeng Fu (Photodiagnosis and Photodynamic Therapy)
Background: The treatment for patients with cervical low-grade squamous intraepithelial lesion (LSIL) and type 3 transformation zone (TZ) had limitations. The aim of this study was to compare the efficacy of new approach 5-aminolevulinic acid photodynamic therapy (ALA-PDT) and observation in those patients. Methods: This study retrospectively analyzed data from 236 patients (aged 25–45 years) with cervical LSIL and type 3 TZ. Participants were divided into ALA-PDT and observation groups, and were followed up for 1-year post-diagnosis. Outcomes were compared and factors influencing LSIL regression and human papillomavirus (HPV) clearance were analyzed. Results: The LSIL regression rate was 89.8 % in the ALA-PDT group, significantly higher than 68.4 % in the observation group (P < 0.05). The ALA-PDT group demonstrated a significantly higher HPV clearance rate of 69.5 % compared to 39.0 % in the observation group (P < 0.05). No significant correlation was found between baseline clinical characteristics and LSIL regression or HPV clearance in either group. Conclusion: ALA-PDT is effective in promoting LSIL regression and HPV clearance. ALA-PDT may be considered as a viable treatment option for women with type 3 TZ, persistent LSIL and high-risk HPV infection, The efficacy of ALA-PDT is not affected by clinical characteristics, suggesting its benefit for patients with various clinical risk factors.